Bifunctional CoFeVOx Catalyst for Solar Water Splitting by using Multijunction and Heterojunction Silicon Solar Cells. Issue 12 (13th November 2020) - Lee, Minoh; Ding, Xinyu; Banerjee, Swarnendu; Krause, Florian; Smirnov, Vladimir; Astakhov, Oleksandr; Merdzhanova, Tsvetelina; Klingebiel, Benjamin; Kirchartz, Thomas; Finger, Friedhelm; Rau, Uwe; Haas, Stefan
Abstract: Photovoltaic driven electrochemical (PV‐EC) water splitting technology is considered as one of the solutions for an environmental‐friendly hydrogen supply. In a PV‐EC system, efficient catalysts are required to increase the rate of both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Here, the development of a CoFeVO x bifunctional catalyst produced by a simple electrodeposition method is presented. It is found that after the water splitting reaction, vanadium is almost completely depleted in the mixture of elements for OER, while its concentration at the HER catalyst is similar or even higher after the reaction. For the OER catalyst, the depletion of vanadium might lead to the formation of pores, which could be correlated with the activity enhancement. The developed catalyst is integrated into PV‐EC devices, coupled with different types of silicon PV. An average solar to hydrogen efficiency of 13.3% (9.6 cm 2 PV aperture area) is achieved with a shingled module consisting of three laterally series‐connected silicon heterojunction solar cells. Abstract : A bias‐free photovoltaic powered water splitting device has been demonstrated with a combination of silicon photovoltaics and electrodeposited ternary cobalt iron vanadium catalysts. The maximum average solar to hydrogen efficiency of 13.31% for 2 h has been obtained with a silicon heterojunction shingled module consisting of three laterally series‐connected solar cells in conjunction with cobalt iron vanadium bifunctional catalysts.